An emotional distress biomarker in pregnant women: Ultra-short-term heart rate variability - Weiyi Xie; Man Wang; Hui Yun Li; Pingqiao Wang; Clifton Robert Emery; Siuman Ng (Biomarkers in Neuropsychiatry)
Prenatal emotional distress is common in pregnant women. Altered emotional distress can occur from the very beginning to the end of pregnancy. Heart rate variability (HRV) has recently become considered to be a potentially reliable psychophysiological stress biomarker in adults. In the current study, we evaluated ultra-short-term HRV (1-minute measurement) as a psychophysiological biomarker by examining the association between HRV parameters and self-reported prenatal emotional distress among pregnant women (N = 230) across three trimesters of pregnancy. Results: Prenatal emotional distress was associated with a lower root mean square of successive differences between normal heartbeats (RMSSD), NN50, and SDNN Index among pregnant women who are in the second trimester. For women in the first and third trimester of pregnancy, prenatal emotional distress was not significantly correlated with any HRV indicators. Limitations: The cross-sectional nature of our results limits the directional expression and assessment of the relationships, and longitudinal studies that target the recruitment of more pregnant women with subtypes of emotional distress issues are also needed. Conclusions: Time-domain parameters of low HRV (associated with reduced parasympathetic activity) can potentially serve as an efficient psychophysiological biomarker for prenatal emotional distress in the second trimester of pregnancy. However, the time-domain HRV indicators in pregnant women in the first and third trimesters may be affected by other physiological and psychological fluctuations, thus decreasing the HRV biomarker’s efficiency in predicting their prenatal emotional distress.